Designing an Engaging and Informative Application About First Aid: Gamification and Humor as Design Elements in a Serious Game - Foldager, Nicolai; Hansen, Hans; Tewes, Mikkel Skovsmose; Bjørner, Thomas (Smart Objects and Technologies for Social Good, 2017)
This study aimed at developing an engaging and informative application within first aid and CPR for people who are already certified in first aid. The paper outlines discussions within definitions of serious games, humor, gamification and engagement. Further we suggest specific elements for implementation and evaluation of humor and gamified elements. Two prototypes were developed: one with gamification elements and one without. A between-group design was used, in which two different groups tested one prototype each. Data were gathered through data logging, in-depth interviews (with use of a verbal numeric rating scale) and observations of participants’ facial expression. The Facial Action Coding System (FACS) was used for analysis. The results showed very little difference between the gamified and non-gamified version. Important elements within gamification are focuses and thoughtfulness within the implementation of challenge, rewards, achievements, feedback and the overall visual theme.